Sulindac Sulfide Inhibits Sarcoendoplasmic Reticulum Ca(2+) ATPase, Induces Endoplasmic Reticulum Stress Response, and Exerts Toxicity in Glioma Cells: Relevant Similarities To and Important Differences From Celecoxib - White, M.C. (2012)
Malignant gliomas have low survival expectations regardless of current treatments. Nonsteroidal anti-inflammatory drugs (NSAIDs) prevent cell transformation and slow cancer cell growth by mechanisms independent of cyclooxygenase (COX) inhibition. Certain NSAIDs trigger the endoplasmic reticulum stress response (ERSR), as revealed by upregulation of molecular chaperones such as GRP78 and C/EBP homologous protein (CHOP). Although celecoxib (CELE) inhibits the sarcoendoplasmic reticulum Ca(2+) ATPase (SERCA), an effect known to induce ERSR, sulindac sulfide (SS) has not been reported to affect SERCA. Here, we investigated these two drugs for their effects on Ca(2+) homeostasis, ERSR, and glioma cell survival. Our findings indicate that SS is a reversible inhibitor of SERCA and that both SS and CELE bind SERCA at its cyclopiazonic acid binding site. Furthermore, CELE releases additional Ca(2+) from the mitochondria. In glioma cells, both NSAIDS upregulate GRP78 and activate ER-associated caspase-4 and caspase-3. Although only CELE upregulates the expression of CHOP, it appears that CHOP induction could be associated with mitochondrial poisoning. In addition, CHOP induction appears to be uncorrelated with the gliotoxicity of these NSAIDS in our experiments. Our data suggest that activation of ERSR is primarily responsible for the gliotoxic effect of these NSAIDS. Because SS has good brain bioavailability, has lower COX-2 inhibition, and has no mitochondrial effects, it represents a more appealing molecular candidate than CELE to achieve gliotoxicity via activation of ERSR.